Hubungan antara Self Esteem dengan Motivasi Berprestasi pada Anggota Paskribra - Edy, bambang; Chintya Dewi, Windy (IDEA: Jurnal Psikologi, 2023)
This research aims to determine the relationship between self-esteem and achievement motivation among Paskibra members of SMK Negeri 3 Jombang. This research involved 38 members of Paskibra SMK Negeri 3 Jombang. The data collection technique was carried out online using google for with purposive sampling technique. Based on the results of the Pearson Product Moment correlation test analysis, the corellation coefficient ® = 0.616 with a significance value of 0.000 (p <0.05) was obtained. There is a significant positive correlation between self esteem and achievement motivation among Paskibra members of SMK Negeri 3 Jombang.